RANCANG BANGUN INTERNET SERVICE PROVIDER (ISP) LOKAL DENGAN JARINGAN WIRRELESS DAN MIKROTIK OS - Rizal Adi Siswanto; Choirul Anam; Sujono - (KH. A. Wahab Hasbullah University, 2018)
Wireless LAN network is a community-based network or community network, why so for the cost of monthly expenditure will be much more affordable than the price of the official ISP. This intenet network is commonly referred to as Local ISP because its coverage area is only inter-district or rural. With the internet it can provide ease of communication process by eliminating the distance and time that has been felt as a factor in particular inhibitors in villages and sub-districts are still rarely affordable telephone cable. Internet network using Wirreless Antenna is expected to provide convenience and comfort of internet access for residents in the Rural. This internet network uses Wirreless antenna as a data transmission medium or internet carrier, and this network uses mikrotik RB 750 where mikrotik here function to manage network traffic. Keywords: Internet, Wireless Antenna, mikrotik RB 750, Local ISP.